SOME ASPECTS OF BIOLOGY OF THE WHITE-SPOTTED SPINE-FOOT, SIGANUS CANALICULATUS (PARK, 1797) FROM THE GULF OF MANNAR - Jayasankar, P (Indian Journal of Fisheries, 2011)
Siganids are excellent food fisheshaving great mariculture potential and someinformation on the biology of this group isavailable (Lam, 1974; Hasse et al, 1977).Works on siganids from Indian v/aters arescanty, being restricted to that of traditionaltrap fishery (Mohan, 1985), food and feeding(Balasubramanyam and Natarajan, 1980),taxonomy (Pius, 1984) and length-weightrelationship (Lazarus and Reddy, 1986-'87).The present study deals with length-weightrelationship, maturation and spawning ofS. canaliculatus from Keelakarai (Gulf ofMannar).MATERIAL